Karyotypic diversity between allopatric populations of the group Hoplias malabaricus (Characiformes: Erythrinidae): evolutionary and biogeographic considerations - Blanco,Daniel Rodrigues (2010)
Three populations of the group Hoplias malabaricus from the hydrographic basins of the São Francisco, Araguaia/Tocantins and Xingu Rivers in Brazil were analyzed using classic cytogenetic methods (Giemsa staining, C-banding and Ag-NORs) and molecular methods (fluorescent in situ hybridization with 18S rDNA, 5S rDNA and 5SHindIII satellite DNA probes). The chromosome markers allowed the characterization of these populations as belonging to karyomorph A and the detection of inter-population divergences. These differences likely stem from different evolutionary histories resulting from geographic isolation between populations associated to the dispersive mode of these organisms, reinforcing genetic diversity in the group Hoplias malabaricus.